The Usage of Cohesive Devices by High-Achieving EFL Students in Writing Argumentative Essays - Andri Saputra; M. Arif Rahman Hakim (Institut Agama Islam Negeri Palopo, 2020)
This study aims to investigate types of cohesive devices frequently used in writing argumentative essays by high-achieving college students in Indonesia and to analyse their awareness of usage of these. Participants were asked to write an essay on a pre-determined topic; analysis was then conducted to investigate the most frequent cohesive devices used. Data on the second study question, understanding of the usage of cohesive devices, were gathered though semi-structured interviews. The data indicate that students effectively used various types of grammatical cohesive devices, particularly reference devices. However, some claimed not to know that they were using other cohesive devices. They believed that conjunctions were the only type that functions to connect ideas across sentences and paragraphs, and did not realise that this, that, the, and other reference devices are cohesive devices. In terms of the use of lexical cohesive devices, participants used synonyms more than other sub-types of lexical cohesive devices. The most frequently used device was the, which functions both as a cohesive device and an article. All participants agreed that though links or cohesive devices are necessary to achieve coherence, two claimed that these are not determining factors in producing good writing quality. They argued that high-quality writing needs to contain linguistic features related to sophisticated language and text difficulty. The first suggestion is that focused programs should be adopted to teach the writing of argumentative essays to help lower-achieving students attain the same writing level as high-achieving students. Second, a teaching programme integrating the use of sophisticated grammar, lexical diversity and cohesive devices should be a curriculum priority.